2023
DOI: 10.3390/md21020123
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Polymicrobial Biofilms of Candida albicans–Staphylococcus aureus/Streptococcus mutans by Fucoidan–Gold Nanoparticles

Abstract: The polymicrobial proliferation and development of complex biofilm morphologies by bacterial and fungal pathogens in the host are some of the key factors contributing to the failure of antimicrobial treatments. The polymicrobial interaction of Candida albicans and some bacterial species has been extensively studied in both in vitro and in vivo model systems. Alternative strategies for disrupting polymicrobial interaction and biofilm formation are constantly needed. Among several alternative strategies, the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The S. aureus and C. albicans biofilms that developed individually or in mixed forms were inhibited in a concentration-dependent manner. Previous studies have shown similar inhibitory effects of AuNPs synthesized using natural compounds against polymicrobial biofilms of S. aureus and C. albicans in a concentration-dependent manner [ 50 ]. However, drug resistance has become a major challenge in eradicating established mature biofilms [ 53 ].…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The S. aureus and C. albicans biofilms that developed individually or in mixed forms were inhibited in a concentration-dependent manner. Previous studies have shown similar inhibitory effects of AuNPs synthesized using natural compounds against polymicrobial biofilms of S. aureus and C. albicans in a concentration-dependent manner [ 50 ]. However, drug resistance has become a major challenge in eradicating established mature biofilms [ 53 ].…”
Section: Discussionmentioning
confidence: 77%
“…The β-c-AuNPs synthesized in this study were found to have antimicrobial activity against S. aureus and C. albicans . Our investigation showed an identical MIC value of β-c-AuNPs against S. aureus and C. albicans , despite the fact that the MIC values of different AuNPs synthesized using naturally derived chemicals show varying activities against various microbial pathogens [ 50 ]. Here, nanoparticles were synthesized using a natural pure compound called β-caryophyllene, which enables the pinpointing of key molecules involved in antimicrobial activity [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations